ANALISIS BUTIR SOAL ISMUBA (AL-ISLAM, KEMUHAMMADIYAHAN DAN BAHASA ARAB) KELAS IV SD MUHAMMADIYAH 5 - LISMAWATI . (Universitas Muhammadiyah Prof Dr Hamka, 2018)
Learning ISMUBA (al-Islam, KeMuhammadiyahan and Arabic) is the key feature of all Muhammadiyah schools. SD Muhammadiyah 5 in Limau South Jakarta is one of the Muhammadiyah elementary school that implemented this learning ISMUBA. The type of this research is descriptive quantitative with qualitative interpretation. This research is conducted in SD Muhammadiyah 5 Jakarta Selatan between September to November 2017. This research population is all class IV students in SD Muhammadiyah 5 South Jakarta. The sample used in this research is saturated population that is all student of Class IV. The collected data includes primary data. Primary data is obtained from the students answer sheet on the subjects of al-Islam, KeMuhammadiyahan and Arabic. Analysis of question items is using IRT (Item Response Theory) through the use of software to see the level of difficulty, distinguishing power. The results obtained from the ITEMAN application will be interpreted in accordance with the provisions of different problem power and problem level.